2021
DOI: 10.1016/j.mayocpiqo.2021.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone Initiation in the Inpatient Setting for Alcohol Use Disorder: A Systematic Review of Clinical Outcomes

Abstract: Alcohol use disorder (AUD) is a highly prevalent health issue in the United States. The number of those receiving medication-assisted treatment (MAT) is limited, despite strong evidence for their effectiveness. The inpatient setting may represent an important opportunity to initiate MAT. The goal of this study was to summarize the data on naltrexone initiation in the emergency department or inpatient setting for the management of AUDs. We searched ClinicalTrials.gov, Ovid EBM Reviews, Ovid Embase, Ovid Medline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Clinical barriers to prescribing naltrexone for AUD may include the risk of hepatotoxicity and a need for patients to be opioid free for a minimum of 7 to 10 days before the drug is begun ( 17 ). Other described barriers are related to prescribers' knowledge and perception of naltrexone treatment for AUD ( 5 , 18 ). To better understand the potential barriers to prescribing naltrexone, a multidisciplinary survey was conducted across 3 sites of a large academic medical enterprise.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical barriers to prescribing naltrexone for AUD may include the risk of hepatotoxicity and a need for patients to be opioid free for a minimum of 7 to 10 days before the drug is begun ( 17 ). Other described barriers are related to prescribers' knowledge and perception of naltrexone treatment for AUD ( 5 , 18 ). To better understand the potential barriers to prescribing naltrexone, a multidisciplinary survey was conducted across 3 sites of a large academic medical enterprise.…”
Section: Introductionmentioning
confidence: 99%
“…To better isolate the effects of the pharmacological interventions, inpatient teams were instructed not to prescribe oral naltrexone (or acamprosate or disulfiram) on discharge, although participants could receive any medication at follow-up if appropriate. Notably, prescribing discharge medications for AUD is rare; a recent systematic review [ 24 ] found just two studies implementing naltrexone prescribing for AUD on discharge. Their baseline prescribing rates were 0.0 and 1.6%.…”
Section: Methodsmentioning
confidence: 99%
“…Their baseline prescribing rates were 0.0 and 1.6%. Additionally, evidence showing effectiveness of in-hospital prescribing of AUD medications is scarce [ 24 ]. Therefore we did not consider lack of oral AUD medication prescription on discharge to be an egregious departure from standard of care.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore used to maintain strict abstinence and should prevent relapse ( Mutschler et al, 2016 ). The other two medications for which the main therapeutic goal is to maintain abstinence due to reduction of alcohol-craving are the NMDA receptor antagonist acamprosate ( Kiefer and Mann, 2010 ), and the long-acting opioid receptor antagonist naltrexone ( Kirchoff et al, 2021 ). Various meta-analyses and reviews have described the effectiveness of these medications in treating alcohol use disorder ( Garbutt et al, 1999 ; Kenna et al, 2004a , 2004b ; Soyka and Roesner, 2006 ; Jonas et al, 2014 ; Soyka and Mutschler, 2016 ).…”
Section: Introductionmentioning
confidence: 99%